Chapter Macao nel XVIII secolo - Graziani, Michela (Studi e saggi, 2023)
The second section of the volume aims to illustrate the iconographical and historical situation of the city of Macao in the 18th century, analyzing the most important volume of the same period written from a Chinese point of view and presenting a Portuguese author who lived in the Portuguese Asia of the 18th century.